Analysis the Level of Students’ Reflective Writing on Their English Language Learning at UKIT - Lendrati, Ratu; Tulaktondok, Linerda; Siumarlata, Viktor (Indonesian TESOL Journal, 2024)
In such situations, reflective writing has become a key tool for the development of literacy skills in general and critical thinking and self-assessment in language acquisition specifically. A study of reflective writing about learning English as a foreign language among adults learners in English Education Students' reflective journals are classified according to their depth, reliance on learning approaches and subjective insights in the study part. This research was qualitative content analysis approach. The participants were 10 second-semester students of the English Education Study Program at UKI Toraja. The findings showed that the majority of students are learning to write reflectively and many still operate on a descriptive level. A small number of students displayed elements of dialogic and critical reflection indicating that all students are capable of attaining the higher levels of reflective writing, if they receive helpful guidance. The results suggest that students indeed share a basic understanding of reflective writing but could do more to express more meaningful insights about their learning process. This research argues for pedagogical consequences and strategies to promote reflective practice in language courses. Keywords: critical thinking, English learning, self-assessment, self-reflection, Reflective writing